The Different Meanings and Levels of Impact of Altmetrics - Kim Holmberg; Fereshteh Didegah; Timothy Bowman (India, 2022)
The idea behind altmetrics is that the online mentions and other indicators of awareness and use of research products could indicate something about the impact of that research. Although some earlier research has found evidence to support this, the meaning of different altmetric events is still somewhat unclear. It would appear that while some of the altmetric events are created by scholars, many are created by the public. If these events could be tracked, it is possible that altmetrics could be a fruitful avenue to investigate societal impact of research. This paper will review some of the earlier research and discuss the potential and caveats of altmetrics.
Emerging Trends and Issues in Scientometrics Informetrics and Webometrics